Wsparcie środkami pomocowymi Unii Europejskiej małych i średnich przedsiębiorstw w województwie łódzkim - Kornecki, Janusz (The Support Given to Small and Medium-Sized Enterprises in the Łódź Province with the Use of the European Union's Assistance Funds, 2009)
This article presents the results of an evaluation study concerning the effects of support given to small and medium-sized enterprises in the Łódź Province with the use of the assistance funds. The study was carried out in September 2008 on the sample of 66 SMEs. The results of the study bring a vague picture of the activeness and effectiveness of applying for EU grants by entrepreneurs from the SME sector located in the Łódź Province. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 655- 662